2017
DOI: 10.1590/s1806-37562016000000075
|View full text |Cite
|
Sign up to set email alerts
|

Association of tuberculosis with multimorbidity and social networks

Abstract: The combination of tuberculosis with other diseases can affect tuberculosis treatment within populations. In the present study, social network analysis of data retrieved from the Mexican National Epidemiological Surveillance System was used in order to explore associations between the number of contacts and multimorbidity. The node degree was calculated for each individual with tuberculosis and included information from 242 contacts without tuberculosis. Multimorbidity was identified in 49.89% of individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
2
5
0
1
Order By: Relevance
“…Our results suggest that male sex, lower levels of wealth and education, smoking, prevalence of NCDs and associated multimorbidity were significantly higher among people with TB than those without a TB diagnosis. Our results are consistent with previous findings: male sex [26,59] and smoking [6,7,60] are two important risk factors for the elevated incidence of TB, and it has also been suggested that people with low educational attainment and poor income are at a higher risk of developing TB [61,62]. The cost of healthcare is a particularly relevant factor in LMICs, where the high healthcare cost relating to NCDs may lead to increased financial restraints and financial burden for accessing preventive health programs and treatment in low-income households [63][64][65].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results suggest that male sex, lower levels of wealth and education, smoking, prevalence of NCDs and associated multimorbidity were significantly higher among people with TB than those without a TB diagnosis. Our results are consistent with previous findings: male sex [26,59] and smoking [6,7,60] are two important risk factors for the elevated incidence of TB, and it has also been suggested that people with low educational attainment and poor income are at a higher risk of developing TB [61,62]. The cost of healthcare is a particularly relevant factor in LMICs, where the high healthcare cost relating to NCDs may lead to increased financial restraints and financial burden for accessing preventive health programs and treatment in low-income households [63][64][65].…”
Section: Discussionsupporting
confidence: 94%
“…Despite this, evidence on NCD multimorbidity in people with TB in these areas remains scarce, with numerous gaps and limitations in the literature. First, most research considering TB multimorbidity-presence of TB alongside one or more chronic conditions-has included small-scale studies [26], been restricted to a single country [4,27,28], or only considered one comorbid chronic condition [29,30]. Second, limited information is available on the actual patterns and risks of multimorbidity compared to the general population and on the burden of disease associated with TB multimorbidity [31].…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that male sex, lower levels of wealth and education, smoking, prevalence of NCDs and associated multimorbidity were significantly higher among people with TB than those without a TB diagnosis. Our results are consistent with previous findings: male sex [ 26 , 59 ] and smoking [ 6 , 7 , 60 ] are two important risk factors for the elevated incidence of TB, and it has also been suggested that people with low educational attainment and poor income are at a higher risk of developing TB [ 61 , 62 ]. The cost of healthcare is a particularly relevant factor in LMICs, where the high healthcare cost relating to NCDs may lead to increased financial restraints and financial burden for accessing preventive health programs and treatment in low-income households [ 63 , 64 , 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite this, evidence on NCD multimorbidity in people with TB in these areas remains scarce, with numerous gaps and limitations in the literature. First, most research considering TB multimorbidity—presence of TB alongside one or more chronic conditions—has included small-scale studies [ 26 ], been restricted to a single country [ 4 , 27 , 28 ], or only considered one comorbid chronic condition [ 29 , 30 ]. Second, limited information is available on the actual patterns and risks of multimorbidity compared to the general population and on the burden of disease associated with TB multimorbidity [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…El Perú tiene una tasa de abandono que para el año 2012 llegó a 5% 4 . Entre los factores relacionados a la falla del tratamiento se han reportado las reacciones adversas a los medicamentos, consumo de alcohol, consumo de drogas y co-infección con virus de inmunodeficiencia humana (VIH) [9][10][11][12] . Además, los problemas de salud mental son factores influyentes en la finalización o abandono del tratamiento [13][14][15] .…”
Section: Introductionunclassified